The Influence Of Brand Experience And Brand Image On Brand Loyalty With Brand Trust As A Mediation Variable (Case Study Of FCL Modest In Pekanbaru City) - Sundari, Laisitha; Djunita Pasaribu, Rina; Sugiat, Maria (International Journal of Science, Technology & Management, 2024)
Famys Circle Label (FCL) is a modest fashion brand that offers thousands of articles from well-known local modest brands in Indonesia and is the only brand in Pekanbaru, giving it a strong competitive edge in the modest fashion market due to its ability to attract a variety of customer groups with diverse tastes and fashion styles. This study aims to examine the effect of brand experience and brand image on brand loyalty, with brand trust as a mediating variable.The research uses a quantitative method with a descriptive approach to illustrate the characteristics of a group, such as the characteristics of users or products, estimate product users' characteristics, and understand users' perceptions of a product. The study uses non-probability sampling, with 384 respondents who are FCL consumers. The data was processed and analyzed using Structural Equation Modeling (SEM) with SmartPLS3 software.The study results show a partial positive and significant effect of brand experience and brand image on brand loyalty and brand trust. Simultaneous testing also showed the same results, where the independent variables had a positive and significant effect on the dependent variable, brand loyalty, mediated by the intervening variable brand trust among FCL consumers in Pekanbaru City.